Comprehensive clinicopathological and molecular analysis of primary malignant melanoma of the oesophagus. Issue 2 (20th September 2020) - Tsuyama, Sho; Kohsaka, Shinji; Hayashi, Takuo; Suehara, Yoshiyuki; Hashimoto, Takashi; Kajiyama, Yoshiaki; Tsurumaru, Masahiko; Ueno, Toshihide; Mano, Hiroyuki; Yao, Takashi; Saito, Tsuyoshi
Abstract : Aims: This study was performed to elucidate the clinicopathological characteristics, genetic alterations and therapeutic targets of primary malignant melanoma of the oesophagus (PMME). Methods and Results: The clinicopathology and molecular pathology of 13 PMME cases and 10 skin malignant melanoma (SKMM) cases were analysed with next‐generation sequencing (NGS) and immunohistochemistry. The 3‐year overall survival rate and the median survival time for PMME patients were 23.1% and 11.9 months, respectively. Three (23.1%) and eight (61.5%) PMME cases showed a papillary structure and lymph node metastasis, respectively. DNA and RNA hybridization capture‐based NGS analysis revealed that NF1 was the most frequently mutated gene (30%) in 10 of the PMME cases. Other mutations detected in PMME included SF3B1 (20%), KRAS (10%), BRCA2 (10%), KIT (10%) and TP53 (10%) mutations. Commonly detected BRAF mutations in SKMM were not detected in PMME. Immunohistochemistry and mutation status were concordant between p53/c‐Kit and TP53 / KIT, respectively. Focal expression of programmed death‐ligand 1 was observed in one PMME sample. The tumour mutation burden in PMME was significantly lower than that in SKMM ( P  = 0.030). No PMME case showed high microsatellite instability. RNA sequencing revealed a distinctive pattern with respect to RNA expression. T‐cell co‐stimulation differed between PMME and SKMM. Conclusions: The RAS–mitogen‐activated protein kinase pathway is one of the main pathways involved in PMME. The genetic profile of PMME was similar to that of mucosal/acral melanoma, but differed from the SKMM profile. A subset of PMMEs may contain actionable mutations. Immunotherapy seemed to be less effective for most PMMEs in this series.